The Markets in Financial Instruments Directive : Banking on Market and Supervisory Efficiency - Haas, Francois (IMF Working Papers; Working Paper, 2007)
The Markets in Financial Instruments Directive (MiFID) which comes to life on November 1, 2007, represents a major step toward the creation of a single, more competitive, cross-border securities market in Europe. Together with other components of the European Commission's Financial Services Action Plan, MiFID has the potential to significantly transform the provision of financial services and the functioning of capital markets in Europe. This paper assesses the directive and the dynamics it creates from a broad perspective, focusing on those aspects that carry relatively higher transformation potential, and on the appropriate supervisory arrangements for European securities markets once MiFID is operational.